Nasal chondromesenchymal hamartoma causing sleep-disordered breathing in an infant - Lee, Cha Hee (Int J Clin Exp Pathol, 2015)
Nasal chondromesenchymal hamartoma is an extremely rare neoplasm of the nasal and paranasal sinuses. We present the case of a 10-month-old boy with a huge nasal chondromesenchymal hamartoma that was complicated by sleep-disordered breathing. The mass was completely resected by image-guided endoscopic surgery and confirmed histopathologically as a chondromesenchymal hamartoma. In this report, we discuss the characteristics and treatment of this unusual tumor.